Coherence Attacks and Countermeasures in Interposer-based Chiplet Systems - Chacon, Gino A.; Williams, Charles; Knechtel, Johann; Sinanoglu, Ozgur; Gratz, Paul V.; Soteriou, Vassos (My University, 2024)
Industry is moving towards large-scale hardware systems that bundle processor cores, memories, accelerators, and so on. via 2.5D integration. These components are fabricated separately as chiplets and then integrated using an interposer as an interconnect carrier. This new design style is beneficial in terms of yield and economies of scale, as chiplets may come from various vendors and are relatively easy to integrate into one larger sophisticated system. However, the benefits of this approach come at the cost of new security challenges, especially when integrating chiplets that come from untrusted or not fully trusted, third-party vendors.In this work, we explore these challenges for modern interposer-based systems of cache-coherent, multi-core chiplets. First, we present basic coherence-oriented hardware Trojan attacks that pose a significant threat to chiplet-based designs and demonstrate how these basic attacks can be orchestrated to pose a significant threat to interposer-based systems. Second, we propose a novel scheme using an active interposer as a generic, secure-by-construction platform that forms a physical root of trust for modern 2.5D systems. The implementation of our scheme is confined to the interposer, resulting in little cost and leaving the chiplets and coherence system untouched. We show that our scheme prevents a range of coherence attacks with low overheads on system performance, g1/44%. Further, we demonstrate that our scheme scales efficiently as system size and memory capacities increase, resulting in reduced performance overheads.
Keywords: Coherence attacks; Coherence systems; countermeasures; interposer Technology